The influence of corporate governance attributes on sustainability reporting: a moderating effect of intellectual capital - Baba, Bello Usman (2019)
Sustainability reporting by corporations has been increasing steadily in both size and complexity over the years. The interest in this area of corporate reporting has been heightened in the modern society, and firms are responding to the interest by actively participating in socially responsible activities and also reflecting same in their annual report or as a discrete report. Thus, the objective of this study is to examine the influence of corporate governance mechanisms on sustainability disclosure in Nigeria. Additionally, the study also examines the moderating effect of intellectual capital on the relationship between corporate governance mechanisms and sustainability disclosure. Data was collected from corporate annual reports, standalone sustainability reports, companies’ websites and Nigeria Stock Exchange (NSE) fact book for the period of six (6) years from 2010 to 2015. This study used convenient sampling for sample selection. The result provides that board size, board independence, board diversity, management ownership, block ownership and foreign ownership are significant and positively related to sustainability disclosure. On the other hand, board meeting is not significantly associated with sustainability disclosure. Meanwhile, the result of the moderation model indicates that board size, board diversity board meetings, management ownership and foreign ownership were significant and positively related to sustainability disclosure after incorporation of intellectual capital as a moderating variable. In contrast, there was no significant effect of board independence and block ownership on sustainability disclosure after inclusion of intellectual capital as a moderating variable. The findings has implication for researchers, corporate managers, policy makers and regulatory bodies. Particularly, the management of Nigerian listed companies who are enjoined to deepen their intellectual capital initiatives and also place greater emphasis on its utilisation to enhance sustainability information disclosure.